INCREASING STUDENT LEARNING ACTIVITIES THROUGH THEMATIC LEARNING IN GRADE 4 OF KUTA BAKMEE STATE ELEMENTARY SCHOOL - Rahmat Alfandi; Humaini; Herda Mutiara; Irhamni; Siti Mayang Sari; Lili Kasmini (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Teachers have a major role in achieving educational goals and studentsuccess, especially in the context of formal learning at school. In an effort todevelop students' potential, teachers are expected to be able to create aninteresting and enjoyable learning atmosphere, using methods, strategies ormethods that activate students to learn. One learning model that can be appliedis thematic learning. This research aims to determine the increase in learningactivities and student learning outcomes through thematic learning in class 4 ofthe Kuta Bakmee State Elementary School. This research uses a descriptivequalitative research method, namely research based on phenomena observed byresearchers in accordance with events that occurred in class 4 of the KutaBakmee State Elementary School. The subjects of this research were classteachers along with several staff and also students who were in grade 4 at theKuta Bakmee State Elementary School, totaling 13 people. This research usesdirect observation techniques, interviews and documentation techniques as datacollection tools. Based on the results of observations and interviews with classteachers, results showed that there was an increase in student activity andlearning outcomes by using thematic learning. So it can be concluded thatthrough thematic learning it can improve learning activities and learningoutcomes for grade 4 students at Kuta Bakmee State Elementary School.